Effects of Eating Behaviors on Being Overweight in Japanese University Students: A Cross-sectional Survey at the Okayama University. (July 2013) - Ekuni, Daisuke; Furuta, Michiko; Tomofuji, Takaaki; Irie, Koichiro; Azuma, Tetsuji; Iwasaki, Yoshiaki; Morita, Manabu
Being overweight is an important risk factor for lifestyle-related diseases. The objective of the present study was to examine whether eating until full, eating quickly, or both eating behaviors were associated with being overweight, defined as a body mass index (BMI) ≥ 25, in young adults. This cross-sectional survey comprised 1918 students (1139 male and 779 female students) at the Okayama University in Japan. In logistic regression analysis, eating until full was not associated with being overweight in either sex. The adjusted odds ratio of being overweight among those who reported eating quickly was 3.93 (2.45-6.31; P < .0001) for male and 1.59 (0.79-3.21; P = .193) for female students. Moreover, the adjusted odds ratio of being overweight was 2.72 (1.72-4.30; P < .001) in male students who frequently reported eating a fatty diet. The combination of eating quickly and frequently eating a fatty diet had a supra-additive effect on being overweight in the male students.